Context-dependent niche variation and fitness consequences in California sea lions - Crawford, Tara Gancos (Author) (2013)
abstract: Niche variation among sexes and life stages within a population has been documented in many species, yet few studies have investigated niche variation within demographic groups or across ecological contexts. We examined the extent to which pregnant California sea lions (Zalophus californianus) at each of three breeding colonies target alternative prey resources and habitats. The three colonies are distributed across distinct regions of the Gulf of California, Mexico and have divergent population dynamics. We compared the nature of niche variation among colonies and investigated the fitness consequences of different foraging strategies within each colony. We analyzed the δ13C and δ15N values from fur collected from 206 suckling pups to characterize relative maternal foraging locations (δ13C) and trophic levels (δ15N) during the metabolically demanding late stages of gestation and lactation that occur simultaneously in California sea lions. The δ13C and δ15N values were regressed against pup body condition index values to compare the relative individual-level fitness benefits of different maternal foraging strategies. We found that the nature and extent of niche variation differed among colonies. Niche variation was most pronounced at the two largest colonies that appear to experience the highest levels of intraspecific competition and the variation was consistent with habitat features. One colony (Granito) displayed two distinct foraging groups with indistinguishable median pup body condition values, whereas the second (San Jorge) exhibited continuous niche variation and pup body condition varied in relation to maternal foraging location and trophic level, suggesting disparities among alternative foraging strategies. For the smallest colony (Los Islotes), females occupy similar niches with a few outliers. Body condition values of pups at this colony were most variable, but did not vary with maternal foraging strategy. Our results provide evidence for intrapopulation niche variation among demographically similar individuals during a period of high metabolic stress and reproductive importance. This work suggests possible fitness benefits conferred by alternative foraging strategies, and calls into question the common assumption that members of a population are ecologically equivalent. Future research aimed at understanding animal foraging strategies should consider the nature and extent of niche variation in the context of local ecological conditions. === Dissertation/Thesis === M.S. Biology 2013